2021
DOI: 10.48550/arxiv.2109.05683
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

AutoSoC: Automating Algorithm-SOC Co-design for Aerial Robots

Srivatsan Krishnan,
Thierry Tambe,
Zishen Wan
et al.

Abstract: Aerial autonomous machines (Drones) has a plethora of promising applications and use cases. While the popularity of these autonomous machines continues to grow, there are many challenges, such as endurance and agility, that could hinder the practical deployment of these machines. The closed-loop control frequency must be high to achieve high agility. However, given the resource-constrained nature of the aerial robot, achieving high control loop frequency is hugely challenging and requires careful co-design of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…7e demonstrates the fault tolerance of three fixed-point data types: Q (1,4,11), Q (1,7,8) and Q (1,10,5) (Q (sign, integer, fraction)) with the same flight quality baseline. We observe that Q (1,4,11) consistently exhibit higher resilience than Q (1,7,8) and Q (1,10,5). This is because Q (1,4,11) has a narrower range compared to others, and are already able to capture the range of weights without performance loss.…”
Section: Inference In Drone Navigation Problemmentioning
confidence: 81%
See 1 more Smart Citation
“…7e demonstrates the fault tolerance of three fixed-point data types: Q (1,4,11), Q (1,7,8) and Q (1,10,5) (Q (sign, integer, fraction)) with the same flight quality baseline. We observe that Q (1,4,11) consistently exhibit higher resilience than Q (1,7,8) and Q (1,10,5). This is because Q (1,4,11) has a narrower range compared to others, and are already able to capture the range of weights without performance loss.…”
Section: Inference In Drone Navigation Problemmentioning
confidence: 81%
“…Autonomous navigation continues to be deployed and attains significant traction in the field of robotics, unmanned drones and autonomous vehicles at all computing scales [1][2][3][4][5][6]. It helps an agent avoid navigating in unknown environments and situations; and take safe actions as needed.…”
Section: Introductionmentioning
confidence: 99%
“…Given the resource-constrained nature of the UAV, achieving high control and managing frequency presents a problematic task [122]. Furthermore, prior studies have shown that computing latency is essential for increasing the computing speed of UAV, which leads to low-power consumption during missing process [123].…”
Section: Discussionmentioning
confidence: 99%
“…MAVFI [41] proposes a fault injection framework for end-to-end reliability characterization of robotic workload, which is portable to robot operating system (ROS)-based applications. Based on AirLearning, Skyline [42], Autopilot [43], and AutoSoC [44] propose a visual performance model and automated design space exploration framework to design optimal onboard compute for aerial robots. Based on PEDRA, Anwar et al [45] present a transfer learning-based approach to reduce the onboard computation required to train a neural network for autonomous navigation.…”
Section: Benchmarking and Software Infrastructurementioning
confidence: 99%